Análise de viabilidade econômica do processo de pirólise para tratamento de resíduos sólidos urbanos : estudo de caso aplicado a uma cidade de médio porte - Caibre, Deise Ieda (2014)
The activities of urban life contribute to accelerate the increase in the amount of waste generated by each individual. The ease in the acquisition of consumer goods accelerate every day, resulting in an increase of the municipal solid waste (MSW) amount in the same proportion. It is important for the sustainability of cities that the solid waste management provides proper disposal of such wastes to prevent environmental damage. Due to the depletion of the areas destined for landfills, the aim of this study is to assess the economic viability of pyrolysis process for treatment of MSW applied to the city of Concordia, SC. In order to meet the main objective, specific goals, including the study of locational alternatives and methods of investment analysis on the condition of certainty, uncertainty and risk were created. The pyrolysis process for MSW was not attractive due to high operational costs and taxes on the sale of electricity and fertilizer. The NPV of the resulting cash flow is negative and there is no return on invested capital for both the enterprise and the investor s cash flow. In this case, the research allowed the study of various scenarios for the economic viability of the project through sensitivity analysis. Considering the possibility of integration with most municipalities to complement the volume of raw material, reducing the cost of transportation of MSW to the plant pyrolysis and increasing the selling price of electricity, or even tax exemption, the project is a cost-effective alternative, due to the fact that, economic benefits aside, the pyrolysis plant allows for the removal of environmental liabilities generated by landfills. Risk analysis of the pyrolysis plant for MSW through the Monte Carlo simulation method was based on the cash flow from the test for determining the parameters on the condition of certainty for pyrolysis, after the sensitivity analysis that showed three different conditions for the viability of the project. Risk analysis of the project showed an amount of 0.5 to 2% of the NPV to be negative, which can be considered negligible for the financial analysis of the business in two scenarios. And a scenario resulted in a risk that ranged from 15% to 20% of the NAV to be negative, which may be considered a significant risk to the project